Low Temperature Sintering and Enhanced Piezoelectricity of Lead‐Free (Na0.52K0.4425Li0.0375)(Nb0.86Ta0.06Sb0.08)O3 Ceramics Prepared from Nano‐Powders. Issue 11 (3rd August 2013) - Huan, Yu; Wang, Xiaohui; Guo, Limin; Li, Longtu
Abstract : (Na0.52 K0.4425 Li0.0375 )(Nb0.86 Ta0.06 Sb0.08 )O3 powders were synthesized via sol–gel and solid‐state reaction methods as a raw material for the preparation of the ceramics. Dependence of piezoelectric properties and microstructure on sintering temperatures was investigated in this study. Sol–gel‐derived nano‐powders could be densified at a lower temperature of 940°C and exhibited excellent electrical properties after sintering at 1020°C ( d 33  = 424 pC/N, d 33 *  = 780 pm/V, k p  = 52.1%, and T c  = 265°C). The enhanced electric properties were most likely due to the coexistence of orthorhombic and tetragonal phase in the samples at room temperature, homogenous microstructure with fine grain and high density.